2009
DOI: 10.1177/0192623309351726
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Molecular Mechanisms of Chemically Induced Neoplasia in Rat and Mouse Models in National Toxicology Program Bioassays and Their Relevance to Human Cancer

Abstract: Tumor response in the B6C3F1 mouse, F344 rat, and other animal models following exposure to various compounds provides evidence that people exposed to these or similar compounds may be at risk for developing cancer. Although tumors in rodents and humans are often morphologically similar, underlying mechanisms of tumorigenesis are often unknown and may be different between the species. Therefore, the relevance of an animal tumor response to human health would be better determined if the molecular pathogenesis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 137 publications
(272 reference statements)
0
31
0
Order By: Relevance
“…In that respect, it is interesting that toxicological studies have shown that the carcinogen o-nitrotoluene, used to synthesize agricultural and rubber products, induces both cecal carcinomas and mesotheliomas in rodent models, possibly through perturbation of the Wnt/b-catenin pathway. 38,39 In summary, our analyses demonstrate that structural alterations involving chr16p13.2 occur frequently in both adenomas and carcinomas. Our data furthermore indicate that the presence of a chr16p13.2 alteration identifies a subgroup of patients with aggressive tumors and poor clinical outcome.…”
Section: Discussionmentioning
confidence: 59%
“…In that respect, it is interesting that toxicological studies have shown that the carcinogen o-nitrotoluene, used to synthesize agricultural and rubber products, induces both cecal carcinomas and mesotheliomas in rodent models, possibly through perturbation of the Wnt/b-catenin pathway. 38,39 In summary, our analyses demonstrate that structural alterations involving chr16p13.2 occur frequently in both adenomas and carcinomas. Our data furthermore indicate that the presence of a chr16p13.2 alteration identifies a subgroup of patients with aggressive tumors and poor clinical outcome.…”
Section: Discussionmentioning
confidence: 59%
“…Identification of early stage biomarkers of NGCs has been previously studied to aid the identification of molecules with carcinogenic potential 3 . Potential biomarkers include increased relative liver weight, hepatocyte labelling index 4 , hepatocellular necrosis, hypertrophy and cytomegally in short term toxicity studies in both rats and mice 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Rodent models lend further support that they were of potential human health risk. Rat had similar response to inflammation and infection as human [10]. In order to establish an animal model for eye research, we used rat eye and the chemical FA to examine corneal injury.…”
Section: Nigella Sativa Groupmentioning
confidence: 99%